(3+3)‐Annulation of Donor–Acceptor Cyclopropanes with Diaziridines. Issue 32 (17th July 2018) - Chagarovskiy, Alexey O.; Vasin, Vladimir S.; Kuznetsov, Vladimir V.; Ivanova, Olga A.; Rybakov, Victor B.; Shumsky, Alexey N.; Makhova, Nina N.; Trushkov, Igor V.
Abstract: The first example of (3+3)‐annulation of two different three‐membered rings is reported herein. Donor‐acceptor cyclopropanes in reaction with diaziridines were found to afford perhydropyridazine derivatives in high yields and diastereoselectivity under mild Lewis acid catalysis. The disclosed reaction is applicable for the broad substrate scope and exhibits an excellent functional group tolerance. Abstract : Beautiful dissymmetry : The first example of (3+3)‐annulation of two different saturated three‐membered rings is reported. Coupling of diaziridines with donor–acceptor cyclopropanes is shown to afford hexahydropyridazine derivatives. This approach can be an efficient tool for the synthesis of diverse nonsymmetric polysubstituted six‐membered rings.